The Effectiveness of Group Counseling with Games and Self-talk Technique to Reduce Communication Apprehension (Universitas Negeri Semarang, 2019)
This study aimed to examine the effectiveness of group counseling with games and self-talk technique to reduce the communication apprehension of the students of Public Senior High School 1 Keo Tengah. The method used was experimental with the design of randomized pre-test – post-test control group design. Meanwhile, it involved 16 subjects chosen through purposive sampling technique from 70 students. The results showed that games and self-talk techniques were effective to reduce communication apprehension by having group counseling with self-talk technique got higher results of the level of effectiveness than games technique. At last, the implication of this counseling has been discussed in the results and discussion session.